Third World Protest: Between Home and The World, Rahul Rao (Meridiano 47 - Journal of Global Studies, 2017)
RAO, Rahul. Third World Protest: Between Home and the World, 2010. Oxford University Press, USA, 288 p. (ISBN 0199560374).